Phenylvinylcobalamin: an alkylcobalamin with a large trans influence - Shin, Naree (My University, 2013)
The synthesis, physical characterization and properties of an alkylcobalamin, phenylvinylcobalamin, is described. Cyanocobalamin was reduced using zinc granules in a 10% acetic acid/methanol solution, before initiating an electrophilic addition reaction on the introduction of phenylacetylene into the reaction mixture under red light conditions. The product was analyzed by HPLC which showed that diastereomers were produced. These two isomers were separated using column chromatography on a C18 stationary phase and characterized by ESI-MS and NMR spectroscopy. One isomer has the phenylvinyl ligand on the upper (β) coordination site of the corrin and the other isomer has the alkyl ligand on the lower (α) coordination site. Whilst the NMR spectrum of the β isomer was virtually fully assigned, the NMR data for the α isomer was not good enough to show the nOe interactions between the phenylvinyl ligand and the corrin ring. ESI-MS strongly suggested that the second isomer was indeed the α isomer, in which the dimethylbenzimidazole (DMB) ligand was displaced from the coordination site of the metal by the alkyl ligand. Photolysis of both products yielded aquacobalamin, confirming that they are both alkylcobalamins. The β isomer was used to achieve the main goal of this work, which was to evaluate the σ donor ability of the phenylvinyl ligand. One of the methods used to evaluate this was the determination of the pKa for the protonation and release of the DMB ligand by a spectrophotometric titration. The greater the σ donor ability of the β axial ligand the greater the charge transferred onto the Co(III) ion; this decreases its Lewis acidity and thus the pKa for protonation and release of the lower DMB ligand should increase. The pKa for β-phenylvinylcobalamin was found to be 4.6(6), which is the highest value yet reported for an alkylcobalamin, confirming the large σ donor ability of phenylvinyl. The pKa for deprotonation of H2O trans to phenylvinyl in α-phenylvinylcobalamin, also determined by spectrophotometric titration, was found to be 13.9(1), which is typical for alkylcobalamins. A further evaluation of the σ donor ability was done by the ligand substitution of DMB by CN– in β-phenylvinylcobalamin and H2O by CN– in α-phenylvinylcobalamin. It was found that log K for substitution of H2O by CN– for the α isomer was 2.70 ± 0.06 and for the displacement of DMB by CN– in the β isomer 0.7 ± 0.1. These values are compared to the values for other alkylcobalamins which are available in the literature, and enabled us to place PhVn in the trans influence order of the cobalt corrinoids. β-Phenylvinyl was crystallized by vapour diffusion of acetone into an aqueous solution of the compound (we were unable to obtain crystals of the α isomer, presumably because of the freedom afforded the f side chain and DMB ligand once it was released from the coordination sphere of the metal). Optical microscopy was used to select a single crystal, the structure of which was determined by X-ray diffraction methods. The compound crystallized in the space group of P21P21P21 with unit cell dimensions a = 15.7783(7) Å, b = 22.3400(9) Å, c = 25.1607(14) Å with four molecules in the unit cell and a calculated density 1.319 Mg m-3, The final R1 values was 9.75%. The axial bond length Co-NB3 to DMB was relatively long (2.225(7) Å) compared to other alkylcobalamins. This is a further indication that phenylvinyl is a powerful σ donor. Overall, this work has allowed us to place phenylvinyl in the σ-donor order of alkyl ligands in alkylcobalmins, i.e. CN–< CCH < CHCH2 = PhVn < Me < Et.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. May 2013
Keywords: Isomerism.; Alkyl.